Repeated-sprint training in hypoxia boosts up team-sport-specific repeated-sprint ability: 2-week vs 5-week training regimen - Shi, Q.; Tong, T. K.; Nie, J.; Tao, D.; Zhang, H.; Tan, X.; Kong, Z. (European Journal of Applied Physiology, 2023)
Purpose To investigate (1) the boosting effects immediately and 4 weeks following 2-week, 6-session repeated-sprint training in hypoxia (RSH2-wk, n = 10) on the ability of team-sport players in performing repeated sprints (RSA) during a team-sport-specific intermittent exercise protocol (RSAIEP) by comparing with normoxic counterpart (CON2-wk, n = 12), and (2) the dose effects of the RSH by comparing the RSA alterations in RSH2-wk with those resulting from a 5-week, 15-session regimen (RSH5-wk, n = 10).